2013
DOI: 10.3201/eid1903.121503
|View full text |Cite
|
Sign up to set email alerts
|

Human Betacoronavirus 2c EMC/2012–related Viruses in Bats, Ghana and Europe

Abstract: We screened fecal specimens of 4,758 bats from Ghana and 272 bats from 4 European countries for betacoronaviruses. Viruses related to the novel human betacoronavirus EMC/2012 were detected in 46 (24.9%) of 185 Nycteris bats and 40 (14.7%) of 272 Pipistrellus bats. Their genetic relatedness indicated EMC/2012 originated from bats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
326
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(354 citation statements)
references
References 15 publications
19
326
2
7
Order By: Relevance
“…reported by Annan et al (2013). In that study, 36.6% of Nathusius's pipistrelles (Pipistrellus nathusii) were positive for MERS CoV-related viruses, whereas only 2.4% of common pipistrelles were positive.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…reported by Annan et al (2013). In that study, 36.6% of Nathusius's pipistrelles (Pipistrellus nathusii) were positive for MERS CoV-related viruses, whereas only 2.4% of common pipistrelles were positive.…”
mentioning
confidence: 92%
“…VM314-related viruses were detected in 15% of fecal samples of Pipistrellus spp. in Europe, including Ukraine and Romania (Annan et al 2013). Lau et al (2013) suggest that MERS CoV has diverged from European bat coronaviruses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, bats are thought to be natural hosts of this virus. This virusis closely related to the Tylonycteris bat coronavirus HKU4 and Pipistrellus bat coronavirus HKU5 and therefore considered to belong to the same species by the International Committee on Taxonomy of Viruses (ICTV) (Annan et al, 2013). Its genomes are phylogenetically classified into two clades, Clades A and B.…”
Section: Etiologymentioning
confidence: 99%
“…The dromedary camel (Camelus dromedarius) has been shown to be the reservoir host for primary human infections 2-8 , although other susceptible animals 9-11 , including bats 12,13 , are suspected also to be hosts for this virus. MERS-like-CoVs have been sequenced from bat samples, mainly from insectivorous bats, but they have not yet been successfully isolated [14][15][16][17][18][19][20][21] . Screening of over 5000 insectivorous bats from Ghana, Ukraine, Romania, Germany, and the Netherlands showed that MERS-CoV-like viruses were detected in 24.9% of Nycteris bats and 14.7% of Pipistrelle bats 17 .…”
mentioning
confidence: 99%